Nitrogen Removal Capacity of Microbial Communities Developing in Compost- and Woodchip-Based Multipurpose Reactive Barriers for Aquifer Recharge With Wastewater - Hellman, Maria; Valhondo, Cristina; Martínez-Landa, Lurdes; Carrera, Jesús; Juhanson, Jaanis; Hallin, Sara (Frontiers in Microbiology, 2022)
Global water supplies are threatened by climate change and expansion of urban areas, which has led to an increasing interest in nature-based solutions for water reuse and reclamation. Reclaimed water is a possible resource for recharging aquifers, and the addition of an organic reactive barrier has been proposed to improve removal of pollutants. There has been a large focus on organic pollutants, but less is known about multifunctional barriers, e.g. how barriers also remove nutrients that threaten groundwater ecosystems. Here we investigated how compost- and woodchip-based barriers affect nitrogen (N) removal in a pilot soil aquifer treatment facility designed for removal of nutrients and recalcitrant compounds by investigating the microbial community composition and their capacity for N-transformations. Secondary treated, ammonium-rich wastewater was infiltrated through the barriers and the changes in ammonium, nitrate and dissolved organic carbon (DOC) concentrations were measured after barrier passage during one year of operation. The development of the community composition in the barriers was determined and potential N-transforming processes in the barriers were quantified by determining the abundances of key functional genes using quantitative PCR. Only one barrier, based on compost, significantly decreased the ammonium concentration in the infiltrated water. However, the reduction of reactive N in the barriers was moderate, between 21 % and 37 %, and there were no differences between barrier types. All barriers were in the end dominated by Alphaproteobacteria, Gammaproteobacteria and Actinobacteria, although the community composition differed. Bacterial classes belonging to the phylum Chloroflexi increased in relative abundances in the compost-based barriers as well as the genetic potential for nitrification. By contrast, potentials for denitrification, nitrous oxide reduction and dissimilatory reduction of nitrate to ammonium increased in the woodchip-based barrier. The barriers have previously been shown to display a high capacity to degrade recalcitrant pollutants but here we show that most barriers performed poorly in terms of N removal and those based on compost also leaked DOC, highlighting the difficulties in designing barriers that satisfactory meet several purposes.